Nutrigenomics and Nutrigenetics in Functional Foods - Romero-Cortes, T.; Lopez-Perez, P. A.; Toledo, A. K. M.; Perez-Espana, V. H.; Aparicio-Burgos, J. E.; Cuervo-Parra, J. A. (International Journal of Bio-resource and Stress Management, 2018)
The main function of the diet is to provide the necessary nutrients to meet the nutritional needs of people. Since long, there is evidence that there is a relationship between diet and health and from these arose the concept of functional foods. In general, functional foods are those that not only fulfill a nutritional function but also contain biologically active components that offer health benefits and reduce the risk of suffering diseases. An important key to know the effect that functional foods have on nutrition is to determine how the body responds to the stimulation of these. In other words, the components of the diet can alter genomic expression. However, not all people respond in the same way. A large number of genes from the human genome are induced to code for the proteins involved in the nutritional processes and the induction of these genes is determined by the polymorphisms that each person has in their genome. For example, a diet rich in folic acid prevents the development of cardiovascular diseases related to people who have a polymorphism in exon 4 of the MTHFR gene related to folate metabolism. Therefore, the proposal of this book is to review the current research of Nutrigenomics, which is the study of the effect of nutrients on the expression of genes and Nutrigenetics which is the influence of polymorphisms of people in response to nutrients.